PENINGKATAN KEUNGGULAN BERSAING MELALUI PENGEMBANGAN MODEL GOOD CORPORATE GOVERNANCE & CORPORATE SOCIAL RESPONSIBILITY PADA SUBHOLDING PERTAMINA HULU ENERGI REGIONAL 1 - Uli Wildan Nuryanto; Sukma Indrakusumah (Universitas Bina Bangsa, 2022)
The increasingly fierce business competition in the current era of globalization, also the high risk that can be caused by the operational activities of companies engaged in oil and gas both to internal and external parties, plus the social problems that can arise from the operational activities of oil and gas companies due to public dissatisfaction have encouraged companies to has a valuable competitive advantage and solves such complex problems, including for Sub holding of Pertamina Hulu Energy regional 1 which is located on Sumatera Island which is famous for being rich in oil and gas, but in reality the poverty rate of the population around the company's operational activities is still very high. For this reason, this research was carried out using GCG and CSR variables as predictors of competitive advantage, where researchers conducted instructions on the variables through the dimensions of each latent variable that would be tested into the research model. The research was conducted for 9 months starting from January to September 2022, using a quantitative approach, survey method and the analysis method using structural equation model (SEM) PLS. The number of indicators used in this study were 32 indicators. The sampling technique used is simple random sampling of 160 respondents to people and community around the company's operational activities. The results show that 32 indicators used in the model have good validity and reliability. The goodness of fit results from the model built have a good predictive relevance with coefficient of determination for economic dimension is 63.3%, while the environmental dimension is 72.3%, the social dimension is 62.9%, and competitive advantage is 81.7 %. The results of the Q2 and GoF index show the model has a high level of model fitness. The results of the fifteen hypotheses proposed in this study are accepted, show the importance of managing the GCG and CSR dimensions to increase competitive advantage of the company